Indicadores de eficiência de produção: uma análise na indústria petroquímica - Adami, Gustavo (Universidade do Vale do Rio dos Sinos, 2015)
Due to singular characteristics present in the production of continuous flow process industry, especially petrochemical, efficiency measurement require different features of intermittently producing industry, such as how to quantify the final products and the cause of the losses that are considered in the calculation of production efficiency. Production efficiency indicators are typically derived from the OEE (Overall Equipment Effective) proposed by Nakajima (1988) for intermittent production industry, they are sometimes used in continuous manufacturing industries without a prior analysis of their limitations. Twelve indicators identified in the literature were analyzed and compared with features of the petrochemical industry production process, obtained from theoretical review and interviews with professionals and researchers in this industry. This analysis identified that the indicator OAE (Overall Asset Efficiency) has a better production losses structure and fits the characteristics of petrochemical manufacturing process. The results of overall production efficiency obtained using the OAE were compared with results from OEE and TEEP (Total Effective Equipment Productivity), based on manufacturing data from a company located in Rio Grande do Sul petrochemical complex. The results obtained from the efficiency calculation utilizing the selected indicator OAE, are more descriptive of the company situation when compared to those currently used. Other practices that causes interference on the calculation of OEE were also identified in the interviews. It was also identified the necessity for a broader discussion in order to better define the concepts of capacity and activity level in the petrochemical industry and also the operational way define them in order to make analysis of efficiency as well as the incorporation of terms concerning the efficiency of inputs and costing the analysis of overall operational efficiency of this industry.
Keywords: Medição de eficiência; Processo contínuo; Petroquímica; OEE (Overall Equipment Effectiveness); TEEP (Total Effective Equipment Productivity); OAE (Overall Asset Effectiveness); Efficiency measurement; Continuous process industry; Petrochemical; ACCNPQ::Engenharias::Engenharia de Produção